Effects of stress relaxation in beta-titanium orthodontic loops: Part II - Junior, Roberto S. S.; Caldas, Sergei G. F. R.; Martins, Lidia P. [UNESP]; Martins, Renato P. [UNESP] (E H Angle Education Research Foundation, Inc, 2016)
Objective: To determine which regions of beta-titanium T-loop springs (TLSs) are more affected by the stress relaxation over a 12-week period. Materials and Methods: Fifty TLS were previously activated by concentrated bends and divided into five groups of 10 each according to their evaluation periods: immediate assessment (GO), 24 hours (G1), 48 hours (G2), 1 week (G3), and 12 weeks (G4). Groups 1 to 4 were mounted into a structure simulating a clinical situation. After the experimental periods, the springs were scanned for measurement of their angles and numbered from 1 to 9. A two-way analysis of variance was used to detect differences among the angles measured and differences caused by time and also to detect interactions between those two factors. Tukey's test was used to find differences among the groups. Results: Time influenced the angulations of the TLSs (P < .001). Tukey post hoc test showed that GO (84.1 degrees) presented a different profile, whereas G1 (90.2 degrees), G2 (90.7 degrees), and G3 (91.1 degrees) had similar profiles among each other, with G4 (92.6 degrees) showing a mean value different from all other groups. A significant interaction was detected between activation time and angular deformation in the TLSs (P < .01). Conclusion: Stress relaxation was observed in the TLSs. It was greatest within 24 hours and gradually increased up to 12 weeks. Two regions were identified as responsible for the relaxation of the TLSs: one at the bend between the vertical extensions of the springs and the base arch and the other at the preactivation bends made in the base arch.
Keywords: Orthodontics; Biomechanics; Titanium